Dihtiaruk N.N., Kurinienko O.V. Inflammatory influenza influenced because of a vertical force - Діхтярук, М. М.; Курінєнко, О. В. (Problems of Tribology, 2018)
In the plane of the linearized theory of elasticity, a plane contact problem is considered about the interaction of an elastic band with initial stresses with an elastic overlay, which is under the action of vertical forces. The influence of initial stresses on the law of distribution of contact forces along the contact line is established. The calculations and graphs for the potentials of the simplest structure: harmonic, Bartenev-Khazanovich and Treloara were constructed.The main guestion is confined in founding out of influence of initial stresses in the band of the law distribution of vertical reactions of interaction between the band with initial stresses and stringers that reinforce the last. Based on the assumption that the stringers are loaded at the same time vertical forces, a fair model of the bending beam in combination with horizontal tension rod, the problem is formulated mathematically as a system of integro-differential equations relative to the unknown contact stresses. Using Fourier transforms, the system is solved inclosed form. Expressions of the stresses are represented by Fourier integrals rather simple structure. The influence of initial stresses on the distribution of the contact stresses and the identified effects of concentrated loads. Stresses in the band are not researching but the formulas that are needed for this are received naturally during problem is standed: received main singular integro-differential equations and on it base formulated general method of considered class of problems solution. Under studied investigations engineering recommendations for constructors are formulated.